Language Acquisition in Children Al Hidayah Kindergarten Kuripan Cilacap: A Psycholinguistic Competence Analysis - Nafisah, Irdina Maziyatun; Rakhmawati, Ani (Universitas Nusantara PGRI Kediri, 2025)
Language acquisition is one of the essential processes in human development, especially during childhood. This process takes place gradually, starting from age 0 through to adulthood. This study aims to analyze the acquisition of the Indonesian language in children aged 4–5 years at Al Hidayah Kuripan Kindergarten, focusing on four psycholinguistic competencies: semantics, phonology, morphology, and syntax. The method used is descriptive qualitative, with data collected through observation, interviews, and document analysis. The results show that the children at Al Hidayah Kindergarten Kuripan have developed the ability to understand word meanings according to context (semantics), produce language sounds with substitution and simplification processes (phonology), form words using affixation and reduplication (morphology), and construct sentence structures such as declarative, imperative, and interrogative sentences (syntax). However, these abilities are still at a basic level, with limited vocabulary and frequent grammatical errors as well as sound mismatches. Additionally, the results indicate that the influence of the mother tongue (Javanese) is present in several aspects, such as the use of non-standard words and distinctive particles. This research contributes to the understanding of early childhood language development and serves as a reference for parents, teachers, and policymakers in supporting effective language learning.